Eriophyoid mites (Acari: Eriophyoidea) on Brassicaceae: a new species of Metaculus from Turkey and remarks on other species associated with brassicaceous plants - Monfreda, Rosita; de Lillo, Enrico (Zootaxa, 2012)
Populations of eriophyoid mites infesting Brassicaceae were surveyed and two species belonging to the genus MetaculusKeifer were found in an attempt to find enemies of some brassicaceous weeds in Turkey. A new species, Metaculus lep-idifolii n. sp., was collected on Lepidium latifolium L., commonly known as broadleaved or perennial pepperweed, man-ifesting leaf curling and deformation. In addition, Metaculus rapistri Carmona, was collected and redescribed from Isatistinctoria L., dyer’s woad, as a new host record and report for the Turkish fauna. This species also causes leaf deformation.A key to all known species of Metaculus found worldwide is provided. Because only a few eriophyoid species have beenrecorded on brassicaceous vegetables and weeds so far and the mite taxonomy appears to be confusing, remarks are given about the current state of knowledge. The new genus combination for Aculops lepidii is also given.